⌊ b a 2 ⌋ + ⌊ a b 2 ⌋ = ⌊ a b a 2 + b 2 ⌋ + a b
Given a and b are positive integers with a < 1 0 0 , if the ordered pairs ( a 1 , b 1 ) , ( a 2 , b 2 ) , … , ( a k , b k ) satisfy the equation above, evaluate i = 1 ∑ k ( a i + b i ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Shoot! I falsely assumed that b < 1 0 0 as well. Oh well, my mistake!
Problem Loading...
Note Loading...
Set Loading...
Let a , b ∈ N satisfy the given equation. It is not possible that a = b (since it leads to a 2 + 2 = 2 a ), so we assume w.l.o.g. that a > b . Next, for a > b = 1 the equation becomes a 2 = 2 a , and one obtains a solution ( a , b ) = ( 2 , 1 ) .
Let b > 1 . If [ b a 2 ] = α and [ a b 2 ] = β , then we trivially have a b ≥ α β . Since also a b a 2 + b 2 ≥ 2 , we obtain α + β ≥ α β + 2 , or equivalently ( α − 1 ) ( β − 1 ) ≤ − 1 . But α ≥ 1 , and therefore β = 0 . It follows that a > b 2 , i.e., a = b 2 + c for some c > 0 . Now the given equation becomes b 3 + 2 b c + [ b c 2 ] = [ b 3 + b c b 4 + 2 b 2 c + b 2 + c 2 ] + b 3 + b c ( c − 1 ) b + [ b c 2 ] = [ b 3 + b c b 2 ( c + 1 ) + c 2 ] . ( 1 ) If c = 1 , then equation ( 1 ) always holds, since both sides are 0 . We obtain a family of solutions ( a , b ) = ( n , n 2 + 1 ) or ( a , b ) = ( n 2 + 1 , n ) . Note that the solution ( 1 , 2 ) found earlier is obtained for n = 1 . If c > 1 , then equation ( 1 ) implies that b 3 + b c b 2 ( c + 1 ) + c 2 ≥ ( c − 1 ) b . This simplifies to c 2 ( b 2 − 1 ) + b 2 ( c ( b 2 − 2 ) − ( b 2 + 1 ) ) ≤ 0 . ( 2 ) Since c ≥ 2 and b 2 − 2 ≥ 0 , the only possibility is b = 2 . But then equation ( 2 ) becomes 3 c 2 + 8 c − 2 0 ≤ 0 , which does not hold for c ≥ 2 .
Hence the only solutions are ( n , n 2 + 1 ) and ( n 2 + 1 , n ) , n ∈ N . And since for this problem a < 1 0 0 answer will be n = 1 ∑ 9 9 ( n 2 + n + 1 ) + n = 1 ∑ 9 ( n 2 + n + 1 ) = 3 3 3 7 3 8